Genomic study for maternal related traits in Santa Ines sheep breed - Amorim, Sabrina Thaise; Kluska, Sabrina [UNESP]; Berton, Mariana Piatto [UNESP]; Antunes de Lemos, Marcos Vinicius [UNESP]; Peripolli, Elisa [UNESP]; Stafuzza, Nedenia Bonvino [UNESP]; Martin, Jesus Fernandez; Saura Alvarez, Maria; Villanueva Gavina, Beatriz; Angel Toro, Miguel; Banchero, Georgget; Oliveira, Priscila Silva; et al. (Elsevier B.V., 2018)
The aim of this study was to estimate variance components and to identify genomic regions and pathways associated with maternal related traits in Santa Ines sheep breed adapted to tropical climate. Phenotypic records for maternal efficiency (ME), metabolic maternal efficiency (MME), twin lambing (TL), adult weight (AW), metabolic adult weight (MAW), and body condition score (BCS) from 1333 ewes from Santa Ines breed were used. A total of 576 animals were genotyped with the Ovine SNP12k BeadChip (Illumina, Inc.), that contains 12,785 bialleleic SNP markers. The variance components were estimated using a single trait animal model by single step genomic BLUP procedure. For AW, MAW, BCS, ME, MME and TL the mean values were 50.30 (+/- 9.76), 19.2 (+/- 2.33), 2.76 (+/- 0.72), 34.6 (+/- 15.95), 91.8 (+/- 42.52), and 1.27 (+/- 0.44), respectively. The heritabilities estimated were moderate for AW (0.32) and MAW (0.33) and low for BCS (0.04), ME (0.07), MME (0.08), and TL (0.10). A total of 7, 8, 13, 16, 19, and 09 candidate regions for ME, MME, TL, AW, MAW and BCS traits were identified, respectively. AW and MAW had a total of 15 regions in common, while AW and BCS had a common region on chromosome 21. ME and MME had six candidate regions in common, and TL had no common regions with any other features. The maternal indicator traits have genetic variability to respond to selection in Santa Ines breed, and it would be expected higher genetic gain for ewe adult weight when compared to the others studied traits. Several candidate regions related to growth, reproduction, lactation and enviromental adaptability were identified in this study. These candidate regions would give support to identify and select animals with higher maternal efficiency and fitness, and consequently, increase the productivity of Santa Ines sheep. Moreover, the results of this study should help to understand the genetic and physiologic mechanism associated with maternal related traits in Santa Ines breed.
Keywords: Body weight; GWAS; Maternal efficiency; Ovis aries